Optimising reef-scale CO2 removal by seaweed to buffer ocean acidification. (16th March 2016) - Mongin, Mathieu; Baird, Mark E; Hadley, Scott; Lenton, Andrew
Abstract: The equilibration of rising atmospheric with the ocean is lowering in tropical waters by about 0.01 every decade. Coral reefs and the ecosystems they support are regarded as one of the most vulnerable ecosystems to ocean acidification, threatening their long-term viability. In response to this threat, different strategies for buffering the impact of ocean acidification have been proposed. As the experienced by individual corals on a natural reef system depends on many processes over different time scales, the efficacy of these buffering strategies remains largely unknown. Here we assess the feasibility and potential efficacy of a reef-scale (a few kilometers) carbon removal strategy, through the addition of seaweed (fleshy multicellular algae) farms within the Great Barrier Reef at the Heron Island reef. First, using diagnostic time-dependent age tracers in a hydrodynamic model, we determine the optimal location and size of the seaweed farm. Secondly, we analytically calculate the optimal density of the seaweed and harvesting strategy, finding, for the seaweed growth parameters used, a biomass of 42 g N m −2 with a harvesting rate of up 3.2 g N m −2 d −1 maximises the carbon sequestration and removal. Numerical experiments show that an optimally located 1.9 km 2 farm and optimally harvested seaweed (removing biomass above 42 g N m −2 every 7 d) increased aragonite saturation by 0.1 over 24 km 2 of the Heron Island reef. Thus, the most effective seaweed farm can only delay the impacts of global ocean acidification at the reef scale by 7–21 years, depending on future global carbon emissions. Our results highlight that only a kilometer-scale farm can partially mitigate global ocean acidification for a particular reef.